Comprehensive Midwifery Care on 34 Weeks Pregnancy with Hemorrhoid - Evy Kasanova; Lidia Widia; Rena Oki Alestari (KHD Production, 2025)
Comprehensive midwifery care is important in providing services to mothers throughout the reproductive life cycle, from pregnancy to family planning. This case study aims to provide comprehensive midwifery care to Mrs. Y, aged 35, with hemorrhoids, using the Varney and SOAP management approaches. This research uses a case study design with the subject, Mrs. Y, who is undergoing midwifery care at the Cempaka Mulya Community Health Center, Cempaga District, East Kotawaringin Regency, Central Kalimantan. Care is carried out comprehensively, covering the third trimester of pregnancy (starting from 34 weeks of gestation), childbirth, newborns, the postpartum period, and family planning planning. Data was collected through observation, interviews, and physical examinations based on midwifery care standards. The research results showed that comprehensive midwifery care was successful. During the observation period, Mrs. Y made four prenatal visits, standard delivery, three newborn visits, four postpartum visits, and one family planning visit. The condition of the mother and baby remains within normal limits without any significant complications related to hemorrhoids. Varney and SOAP management approaches effectively identify and manage physiological conditions and ensure maternal and infant health. Comprehensive midwifery care with the Varney management approach and SOAP can support the handling of physiological cases such as Mrs. Y with hemorrhoids. The results of this study show that early detection and intervention, according to midwifery care standards, can prevent serious complications in mothers and babies. The patient's active participation also influences the success of this care in every stage of routine examinations and visits. Comprehensive midwifery care applied to Mrs. Y with hemorrhoids succeeded in maintaining the good condition of the mother and baby during the cycle of pregnancy, childbirth, postpartum, and family planning. Varney's management approach and SOAP have proven effective in providing holistic and quality midwifery services.